The illusion of comparable European IFRS financial statements. Beliefs of auditors, analysts and other users - Vicky Cole; Joel Branson; Diane Breesch (Journal of Accounting and Management Information Systems (JAMIS), 2011)
Reaching higher comparability was one of the main goals of the implementation of the International Financial Reporting Standards (IFRS) in the European Union in 2005. However, national accounting traditions and cultural differences continue to cause differences in the application of IFRS (KPMG & von Keitz, 2006). European IFRS financial statements might therefore be less comparable than users of these statements possibly assume. This study contributes by determining to what extent auditors, analysts and other users of European IFRS financial statements believe that these statements are comparable and what they perceive to be the most important problem areas when it comes to comparability. Our survey of 426 individuals reveals that only 41% of the respondents believe that European IFRS financial statements are comparable. The more experienced respondents are, the less they believe in the comparability of these statements. Overall, 13 areas are perceived as problematic for the comparability of IFRS financial statements by at least half of the respondents. The three main issues that appear in most of these problem areas are interpretation differences, subjectivity and disclosure differences.
Keywords: M41; 650; Comparability; European IFRS financial statements; survey